Peningkatan Pemahaman Tentang Pencegahan Pernikahan Dini Dan Pergaulan Bebas Berdasarkan Undang-Undang Perlindungan Anak Melalui Kegiatan Sosialisasi Di Sekolah Menengah Kejuruan (SMK) Negeri 2 Padang - Marwenny, Elwidarifa; D Khotni, Raka Surya; Ramadani, Dewi; Hartanto, Agung; Rahayu, Dwi; Zukrullah, Luqfi; Ananda, Anissa Putri; Rahma M, Aisyah Dwie; Riffah, Rahmah; Arisca R, Laurencia; Putra, Ilham Hidayat; Siddiq, Zahran Arsa; Aliano, Putri; Febrian, Ghani; Buana A, Ripo Cakra (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
Early marriage is a pressing socio-demographic issue in Indonesia, often triggered by the phenomenon of promiscuity among adolescents. Promiscuity, defined as interaction without religious, social, or ethical norms, significantly increases the risk of premarital sexual behavior, which in turn leads to unwanted pregnancy (KTD). Disrupted education and lack of emotional maturity make early marriage a persistent problem, creating an intergenerational cycle of vulnerability. Early marriage can negatively impact the health, education, and well-being of children and adolescents.